POTENSI PROPOLIS Trigona sp. TERHADAP JAMUR PENYEBAB KANDIDIASIS VULVOVAGINAL - Dinda Oktia Maghfiroh (LPPM Widyagama Husada Malang, 2025)
Vulvovaginal candidiasis is a vulvar and/or intravaginal infection that often attacks women of reproductive age. The most common cause of this infection is Candida albicans. C. albicans has a high ability to form biofilm. Biofilm is a virulence form of C. albicans and a major cause of antifungal drugs resistance. One alternative that can be used is propolis. Propolis is a wax mixed with resin produced by honey bees as a result of a collection of substances released by plants. The type of bee that produces the most propolis is Trigona sp. This review aims to describe a comprehensive overview of the potential of Trigona sp. propolis against fungi that cause vulvovaginal candidiasis, especially C. albicans. The research method is a literature review with data sources in the form of true experimental research articles from both national and international journals via Google Scholar, PubMed, Elsevier, and Researchgate. Literature studies show that propolis Trigona sp. from several regions in Indonesia, Nepal and Malaysia is known to contain flavonoid compounds which have antifungals and antibiofilms potential against C. albicans (major cause of vulvovaginal candidiasis).